A multifunctional nanofiber reinforced photo-crosslinking hydrogel for skin wound healing. (December 2022) - Yu, Fan; Khan, Atta ur Rehman; Li, Yaqiang; Zhao, Binan; Xie, Xianrui; EL-Newehy, Mohamed; EL-Hamshary, Hany; Morsi, Yosry; Li, Jun; Pan, Jianfeng; Mo, Xiumei
Abstract: Acute skin wounds often lead to tissue defects and bacterial infection, leading to the suffering of patients. In this study, we reported a multifunctional nanofiber reinforced photo-crosslinking hydrogel wound dressing mainly based on natural biomaterials to mimic the structure and components of the native extracellular matrix (ECM). Gelatin-methacryloyl (GelMA), Thioglycolic acid-modified chitosan (TCS) and 3-buten-1-amine (BA) modified polycaprolactone nanofiber (PCLPBA) were prepared and photo-crosslinked into GTP hydrogel. Among all hydrogels, the GTP4 hydrogel possessed rapid liquid-gel transition at ultraviolet (UV) exposure, excellent antibacterial effect, antioxidant property, and printability through 3D printing. Besides, NIH 3T3 cells proliferated well and invaded GTP4 hydrogel. When it was applied to the full-thickness skin defect, GTP4 hydrogel showed the enhanced angiogenesis, re-epithelialization and wound healing effect. Therefore, these findings indicate that the GTP4 hydrogel is a promising wound dressing for acute skin wounds.